Ultrawide Bandgap and High Sensitivity of a Plasmonic Metal-Insulator-Metal Waveguide Filter with Cavity and Baffles - Chou Chau, Yuan-Fong (Nanomaterials (Basel), 2020)
A plasmonic metal-insulator-metal waveguide filter consisting of one rectangular cavity and three silver baffles is numerically investigated using the finite element method and theoretically described by the cavity resonance mode theory. The proposed structure shows a simple shape with a small number of structural parameters that can function as a plasmonic sensor with a filter property, high sensitivity and figure of merit, and wide bandgap. Simulation results demonstrate that a cavity with three silver baffles could significantly affect the resonance condition and remarkably enhance the sensor performance compared to its counterpart without baffles. The calculated sensitivity (S) and figure of merit (FOM) in the first mode can reach 3300.00 nm/RIU and 170.00 RIU(−1). Besides, S and FOM values can simultaneously get above 2000.00 nm/RIU and 110.00 RIU(−1) in the first and second modes by varying a broad range of the structural parameters, which are not attainable in the reported literature. The proposed structure can realize multiple modes operating in a wide wavelength range, which may have potential applications in the on-chip plasmonic sensor, filter, and other optical integrated circuits.